Elastomeric nanocomposite based on exfoliated graphene oxide and its characteristics without vulcanization - Habib, Nasser Abdullah; Chieng, Buong Woei; Mazlan, Norkhairunnisa; Rashid, Umer; Yunus, Robiah; Abdul Rashid, Suraya (Hindawi Publishing Corporation, 2017)
Rubber nanocomposites have emerged as one of the advanced materials in recent years. The aim of this work was to homogeneously disperse graphene oxide (GO) sheets into Nitrile Butadiene Rubber (NBR) and investigate the characteristics of GO/NBR nanocomposite without vulcanization. A suitable solvent was found to dissolve dry NBR while GO was exfoliated completely in an aqueous base solution using sonication. GO was dispersed into NBR at different loadings by solution mixing to produce unvulcanized GO/NBR nanocomposites. Scanning Electron Microscopy (SEM), Fourier-Transform Infrared Spectroscopy (FTIR), and X-Ray Diffraction (XRD) were used to characterize the samples. Furthermore, mechanical and electrical properties of unvulcanized GO/NBR nanocomposites were carried out to determine the influence of GO on the NBR properties. The results showed that the modulus of GO/NBR nanocomposite at 1 wt% of GO was enhanced by about 238% compared with unfilled NBR. These results provide insight into the properties of unvulcanized GO/NBR nanocomposite for application as coatings or adhesives.